2005
DOI: 10.1590/s1519-566x2005000600011
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e exigências térmicas de Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) em ovos de Bonagota cranaodes (Meyrick) (Lepidoptera: Tortricidae)

Abstract: Neotropical Entomology 34(6): 945-949 (2005) Development and Thermal Requirements of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) on Eggs of Bonagota cranaodes (Meyrick) (Lepidoptera: Tortricidae)ABSTRACT -The aim of this study was to evaluate the development of Trichogramma pretiosum Riley on eggs of Bonagota cranaodes (Meyrick) under different temperatures. B. cranaodes eggs were maintained under seven constant temperatures (14, 18, 20, 22, 25, 28 and 30ºC), 70 ± 10% R.H. and, 14 h L. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
1
5
0
9
Order By: Relevance
“…Molina and Parra (2006) have reported similar results obtained with eggs of Gymnandrosoma aurantianum Lima (Lepidoptera: Tortricidae) in which they found a variation between 1.4 and 1.8 individuals/egg at 25ºC. The values found in this study, however, are higher than the figures determined for other species of pest lepidopterans such as Bonagota cranaodes Meyrick (Lepidoptera: Tortricidae) and Chrysodeixis includens Walker (Lepidoptera: Noctuidae) FONSECA et al, 2005). These authors reported values of 1.3 and 1.0 individuals/egg, respectively, at 25ºC.…”
Section: Resultssupporting
confidence: 79%
“…Molina and Parra (2006) have reported similar results obtained with eggs of Gymnandrosoma aurantianum Lima (Lepidoptera: Tortricidae) in which they found a variation between 1.4 and 1.8 individuals/egg at 25ºC. The values found in this study, however, are higher than the figures determined for other species of pest lepidopterans such as Bonagota cranaodes Meyrick (Lepidoptera: Tortricidae) and Chrysodeixis includens Walker (Lepidoptera: Noctuidae) FONSECA et al, 2005). These authors reported values of 1.3 and 1.0 individuals/egg, respectively, at 25ºC.…”
Section: Resultssupporting
confidence: 79%
“…O total de ovos parasitados por T. pretiosum linhagem bonagota a 25°C, foi superior aos resultados obtidos por Fonseca (2001) estudando o parasitismo de quatro linhagens de T. pretiosum de ovos de B. salubricola (=cranaodes). De acordo com Pereira et al (2007) as diferenças na quantidade e uniformidade de parasitismo pelas espécies, podem estar relacionadas à habilidade específi ca desses parasitóides em conseguir introduzir o ovipositor no cório do ovo hospedeiro, uma vez que o mesmo perde gradativamente a turgidez com o aumento da temperatura.…”
Section: Resultsunclassified
“…Esses resultados foram semelhantes aos obtidos por Hansen & Jensen (2002) trabalhando com Trichogramma turkestanica Meyer em ovos de Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae). Fonseca (2001), trabalhando com T. pretiosum em ovos de B. salubricola (=cranaodes) a 25°C, relatou longevidade superior, para as quatro linhagens estudadas, quando comparada a esta pesquisa para a mesma temperatura. De acordo com Bleicher & Parra (1989), a redução na temperatura promove aumento na longevidade dos parasitóides, uma vez que ocorre redução na taxa de metabolismo dos mesmos.…”
Section: Resultsunclassified
“…The parasitism rate can vary with physical and chemical barriers and by the type and characteristics of host eggs such as their size, hardness, scales and kairomones or differences in fertility among species of parasitoids (BESERRA; PARRA, 2004;SOARES et al, 2006;SOARES et al, 2009;SOARES et al, 2012). Temperature can also affect the parasitism capacity, with many Trichogramma species presenting maximum fertility between 21 and 30ºC that decreases at extreme temperatures (DA FONSECA et al, 2005;PRASAD et al, 1999;ZAGO et al, 2007). Life tables for T. pretiosum and Trichogramma atopovirilia (Oatman; Platner) (Hymenoptera: Trichogrammatidae) reared with Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) eggs showed higher specific fertilities for the first species with all temperatures tested (NAVARRO; MARCANO, 2000).…”
Section: Resultsmentioning
confidence: 99%